Food insecurity, home ownership and income-related equity in dental care use and access: the case of Canada - Margherita Giannoni; Michel Grignon (BMC, 2022)
Abstract Background It has been documented that income is a strong determinant of dental care use in Canada, mostly due to the lack of public coverage for dental care. We assess the contributions of food insecurity and home ownership to income-related equity in dental care use and access. We add to the literature by adding these two variables among other socio-economic determinants of equity in dental care use and access to dental care. Evidence on equity in access to and use of dental care in Canada can inform policymaking. Methods We estimate income-related horizontal inequity indexes for the probability of 1) receiving at least one dental visit in the last 12 months; and 2) lack of dental visits during the 3 years before the interview. We conduct the analyses using data from the 2013-2014 Canadian Community Health Survey (CCHS) at the national and regional level. Results There is pro-rich inequity in the probability of visiting a dentist or an orthodontist and in access to dental care in Ontario. Inequities vary across jurisdictions. Housing tenure and food insecurity contribute importantly to both use of and access to dental care, adding information not captured by standard socio-economic determinants. Conclusions Redistributing income may not be enough to reduce inequities. Careful monitoring of equity in dental care is needed together with interventions targeting fragile groups not only in terms of income but also in improving house and food security.